Proteomic Profiling Methods and Protocols - Posch, Anton.; Posch, Anton. (Methods in Molecular Biology, 2015)
This volume presents the latest developments of the main pillars of protein analysis, such as sample preparation, separation, and characterization. The book begins by describing basic but important sample preparation protocols. It then goes on to describe more sophisticated procedures on enriching specific protein classes, and concludes with detailed descriptions of integrated work-flows for comprehensive protein analysis and characterization. The authors of the individual chapters are renowned protein biochemists who have all set value to provide a detailed representation of their lab work. Throughout the chapters, these authors share important tips and tricks for a successful and reproducible employment of their protocols in other laboratories. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Proteomic Profiling: Methods and Protocols is the perfect guide for students of Biochemistry, Biomedicine, Biology, and Genomics and will be an invaluable source for the experienced, practicing scientists.